2018
DOI: 10.1021/acsami.8b09939
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Solid Electrolyte Interphase on the Carbonaceous Electrodes Using Soft X-ray Absorption Spectroscopy

Abstract: It is widely accepted that solid electrolyte interphase (SEI) layer of carbonaceous material is formed by irreversible decomposition reaction of an electrolyte, and acts as a passivation layer to prevent further decomposition of the electrolyte, ensuring reliable operation of a Li-ion battery. On the other hand, recent studies have reported that some transition metal oxide anode materials undergo reversible decomposition of an organic electrolyte during cycling, which is completely different from carbonaceous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…at 298K (5) Unlikely, in a quasi-reversible process which show limitation of electron transfer kinetics, the peak potential is a function of scan rate. Li + intercalation reactions tend to follow a quasi-reversible process since cathodic and anodic peaks are dependent on the scan rate [15].…”
Section: Equations Of Voltammetry For Intercalation Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…at 298K (5) Unlikely, in a quasi-reversible process which show limitation of electron transfer kinetics, the peak potential is a function of scan rate. Li + intercalation reactions tend to follow a quasi-reversible process since cathodic and anodic peaks are dependent on the scan rate [15].…”
Section: Equations Of Voltammetry For Intercalation Systemmentioning
confidence: 98%
“…Li ion battery has the best performance among rechargeable batteries that are currently in commercial use and is widely used in portable products such as mobile phones, laptops, power tools, and electric vehicles. In addition, due to technological advances, the performances required for Li ion batteries such as high capacity long cycle life have been gradually enhanced [1][2][3][4][5][6]. Looking at the Li ion batteries, electrochemical reactions take place in the electrodes, and even in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…They later designed another NASICON-structured Na 3 MnTi(PO 4 ) 3 cathode for SIBs and found that both solidsolution and two-phase transformation reactions occur in this material during electrochemical cycling. 122 As illustrated in Figure 9d, the diffraction peaks ( 104), ( 113), (204), and (300) exhibit reversible shifts during cycling, indicating a solidsolution reaction. Meanwhile, presence/absence of ( 211) and ( 116) peaks indicate a biphasic reaction.…”
Section: In Situ/operando Xrdmentioning
confidence: 94%
“…Kim and co-workers collected C K-edge spectra in ether-based electrolytes for graphite and carbonate-based electrolytes for hard carbon/soft carbon (Figure ). Peaks B, C, D, and F are interpreted as Na 2 CO 3 and some other complex organic sodium salts. The intensity change represents the disappearance and re-development of SEI.…”
Section: In Situ/operando Xasmentioning
confidence: 99%
“…Therefore, this conclusion still needs more evidences from other techniques. Moreover, some works on Na-storage properties of graphite suggest that the reduced products were soluble in the case of ether-based electrolytes [30][31][32] , thus no SEI lm was detected. Although HC and graphite have some differences in structures, they still share the similar element, unique graphene layers, and so on.…”
Section: Introductionmentioning
confidence: 99%